Vaccination patterns, disparities, and policy among Asian-Americans and Asians living in the USA - Armaan Jamal; Ryan Wang; Ziqing Wang; Shozen Dan; Malathi Srinivasan, MD; Gloria Kim, MD; Latha Palaniappan, MD; Jaiveer Singh; Shanthi Kappagoda, MD (Elsevier, 2022)
Background: Although Asian-American individuals have higher rates of some vaccine-preventable diseases such as hepatitis B, vaccination rates among them are low compared with those of non-Hispanic White individuals. Most vaccine research looks at Asian-American people as a single category despite large within-group heterogeneity in health-seeking behaviours. Little is known about vaccination coverage among disaggregated Asian-American ethnic subgroups, although such information could inform policies focused on increasing vaccine uptake. Therefore, we aimed to assess vaccination coverage for several vaccines among disaggregated Asian-American subgroups. Methods: We examined National Health Interview Survey (NHIS) data from 2015-18 to analyse the vaccination status of Chinese, Asian Indian, Filipino, other Asian, and non-Hispanic White adults (n=253 626) for seven vaccines recommended by the US Centers for Disease Control and Prevention: human papillomavirus (HPV), hepatitis B (HBV), influenza, tetanus, tetanus-diphtheria-pertussis (Tdap), shingles, and the pneumococcal vaccine. We used NHIS data from 2006-18 (n=880 210) to analyse changes in vaccination rates for each ethnic group over time. We used logistic regression to estimate differences in vaccination rates while controlling for demographic, socioeconomic and health-related variables. Findings: Among the seven vaccines, HPV and shingles vaccines had the lowest uptake, whereas Tdap had the highest uptake among all groups. Compared with the non-Hispanic White group, Asian Indians were almost half as likely to receive the HPV vaccine (odds ratio 0·61, 95% CI 0·41-0·92), whereas Filipinos (1·51, 1·02-2·25) and other Asians (1·42, 1·02-1·97) were more likely to receive it. The Filipino (1·50, 1·21-1·88) and other Asian groups (1·42, 1·19-1·71) were more likely to receive the HBV vaccine than the non-Hispanic White group. For the influenza vaccine, the Asian Indian (1·28, 1·05-1·56), Filipino (1·44, 1·17-1·79) and other Asian (1·38, 1·16-1·65) groups were more likely to receive the vaccine than the non-Hispanic White group. For the pneumococcal vaccine, the Chinese (0·57, 0·34-0·94) and other Asian (0·66, 0·47-0·92) groups were less likely to receive the vaccine than the non-Hispanic White group. Interpretation: Among US adults, we found significant disparities in vaccine uptake among different Asian and Asian-American ethnic groups. US policy makers trying to improve vaccine uptake among Asian and Asian-American people could learn from successful international immunisation programmes to develop culturally appropriate interventions to improve vaccine uptake in Asian and Asian-American individuals. Funding: None.